Phonetic recalibration does not depend on working memory - Baart, Martijn (Springer-Verlag, 2010)
Listeners use lipread information to adjust the phonetic boundary between two speech categories (phonetic recalibration, Bertelson et al. 2003). Here, we examined phonetic recalibration while listeners were engaged in a visuospatial or verbal memory working memory task under different memory load conditions. Phonetic recalibration was—like selective speech adaptation—not affected by a concurrent verbal or visuospatial memory task. This result indicates that phonetic recalibration is a low-level process not critically depending on processes used in verbal- or visuospatial working memory.